Short term, low strain radial tensile stiffness of a triaxial geogrid with integral junctions - Stowell, Paul A. (2020)
This work starts by introducing the triaxial geogrid to be tested, TriAx®, along with its intended use and applications. It identifies that stabilisation and interlock is well understood but the radial, low-strain, tensile load-strain stiffness of these geogrids is not. A detailed review of the development of geogrids with integral junctions is then undertaken, highlighting how geogrids were first produced in the 1950’s and how they have been developed up to the point of starting this work. Index and performance testing of geogrids with integral junctions are described. The specific geogrid for testing, TriAx® TX160, is introduced along with the methods of testing and the test programmes defined. Q.C., Index, and uniaxial creep testing is defined, carried out, and the data analysed and compared. A secondary crystallisation mechanism is established and occurs over time after production. Quadrant radial creep testing of TriAx® TX160 geogrid is introduced. To date wide-width, uniaxial constant rate of strain (CRS) tensile tests carried out in multiple directions have been used to determine the radial stiffness property, but the validity of this approach has not been investigated. Therefore, a new, in-plane, radial tensile test apparatus and test methodology has been developed for this purpose. The apparatus and sample geometry are defined, and the test data and analysis presented. All low strain behaviour from the three different test methodologies, constant rate of strain, uniaxial creep, and radial creep, were combined and compared with a possible “locked-in stress” being identified. The data from all three test methodologies are replotted with the possible locked-in stress. Upon comparing data obtained from this new radial tensile test and multi-directional uniaxial tensile testing, the data was found to be closely correlated. Thus, the multi-directional, uniaxial CRS tensile test is shown to be a reasonable and conservative means of determining the short-term, low-strain, radial tensile stiffness of multi-axial geogrids and the need for more elaborate testing methodologies is not required.